Correlation Between VEGF and EGFR Expression in Urothelial Carcinoma of Bladder - Anny Setijo Rahaju, Anny
Abstract Bladder cancer is the ninth malignancy of the genitourinary system in the world. Urothelial cell carcinoma is the commonest histological type. There are no good therapeutic options to date. Vascular endothelial growth factor (VEGF) is a growth factor that is essential to stimulate angiogenesis. Tumor growth relies on angiogenesis and determines the therapy. The epidermal growth factor receptor (EGFR) is known as a tyrosine kinase transmembrane receptor. EGFR is involved in the regulation of VEGF. Several researches have shown that EGFR stimulation induces VEGF expression. Therefore, this research was conducted to analyze the relationship between VEGF and EGFR, as the basis of therapy using anti-VEGF and anti-EGFR. An observational research was conducted on 53 formalin fixed paraffin-embedded tissue from Radical Cystectomy patients urothelial carcinoma of bladder which was at Dr. Soetomo General Academic Hospital Surabaya, Indonesia during 2010 - 2019. Immunohistochemistry was conducted using VEGF and EGFR antibodies. Significant positive correlation was seen between EGFR and VEGF expression in bladder urothelial carcinoma. VEGF and EGFR expression can use as the basis of therapy using anti-VEGF and anti-EGFR in bladder urothelial carcinoma.